A Retrospective Analysis of the Clinical Features of Inpatients With Epilepsy in the Ganzi Tibetan Autonomous Prefecture - Chen, Jiani; Wu, Xintong; He, Yongqiao; Li, Sisi; Deng, Yongyi; Chen, Jie; Fang, Wenyu; Zeren, Zhamu; Peng, Jianmei; Li, Yingjuan; Mu, Jie; Zhou, Dong (Frontiers in Neurology, 2018)
Background: There is limited detailed clinical information for patients with epilepsy in Tibet. This study sought to provide data about the clinical features of epilepsy in the Ganzi Tibetan Autonomous Prefecture to improve strategies for epilepsy prevention and control in this region. Methods: We reviewed the clinical record of patients with epilepsy in the Neurology Department, Ganzi Tibetan Autonomous Prefecture People's Hospital and had summarised their clinical features and compared it with control. Results: This retrospective study included 165 patients with epilepsy admitted between January 2015 and February 2018. Majority of patients (97%) in this study had active epilepsy; 28.5% had generalized onset seizures and 68.5% had focal onset seizures. Fifty-four had received anti-epileptic drug (AED) treatment prior to hospitalization. However, 38 (70.4%) patients used this medication irregularly. Among the patients, the leading etiology cause was head trauma (20.6%), followed by stroke (10.9%), neurocysticercosis (7.9%), brain hydatidosis (6.7%) and tuberculous infection (5.5%). Compared with in-patients in Chengdu, epilepsy in Ganzi was more frequently caused by infection (OR=4.216, 95% CI, 2.124-8.367), including neurocysticercosis (OR=29.301, 95% CI, 1.727-497.167) and brain hydatidosis (OR=24.637, 95% CI, 1.439-421.670). Conclusions: These data suggest that the control of cerebral infections, especially parasite infection, is essential for the prevention of epilepsy in the Ganzi Tibetan Autonomous Prefecture. Education of local primary doctors and patients about seizures will enable better management of epilepsy in this population.